Student Satisfaction Level Of IHDN Denpasar Services (Analysis of Hindu Religious Education) - I Ketut Sudarsana; Anak Agung Ayu Alit Widyawati (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2020)
This study aims to analyze the level of student satisfaction with the services of the Denpasar Hindu Dharma Negeri Institute (IHDN Denpasar). The study's results are used to perform quality control as well as the development both in academic and non-academic. So that the quality of graduates increases. The rapid flow of globalization and the effects of the industrial revolution 4.0 forced each university to make various innovations so that service quality is maintained and improved. IHDN Denpasar, as a state religious college under the Ministry of Religion, is demanded to have quality service to remain in the people's choice. One of the evaluation tools to find out the level of service quality to students can be used survey.This study is survey-based research. The subjects in this study were active students of IHDN Denpasar in the even semester of the academic year 2018/2019. The aspects reviewed to determine the satisfaction of IHDN Denpasar services are based on five indicators established by the National Accreditation Board for Higher Education, namely; Reliability, responsiveness, assurance, empathy, and tangible. The sampling technique is done by proportionate stratified random sampling. The Data collection techniques using attitude scale. The data analysis technique was using trend test and the percentage of the frequency distribution for each aspect of satisfaction. Based on the results of the study found the number of students who feel less satisfied as much as 2%, 25% satisfied enough, 51% satisfied, and 22% very satisfied. The conclusion that can be drawn based on the percentage of the total respondents stated that most of them were pleased with the services provided by IHDN Denpasar.